Analisa Motivasi dan Persepsi Masyarakat Surabaya Dalam Memilih Destinasi Wisata ke China - Kusnaidy, Regina Cecilia (Tourism Retailing+, 2013)
This research is to analyze the motivation and perception of Surabaya residence related with their profile respondents toward China as tourism destination. To get the best result the writer uses cross tabs as the device to analyze the sources which is collected from 100 respondents.